Comparative Analysis of Labor Productivity Coefficient Based on Standardization of Indonesian National Standard 7394:2008 and Regulation of the Minister of Public Works and Housing of the Republic of Indonesia No. 28 of 2016 on Column Fixing Work - Sombolayuk, Gerry Geraldo; Tanjung, Novita (East Asian Journal of Multidisciplinary Research, 2024)
Construction projects are complex activities that require control of each element. One part of the element that needs to be considered is labor. In Indonesia, general provisions on construction project reference standards have developed since the colonial era known as BOW (Burgeslike Openbare Werken). Over time, BOW analysis has been replaced by SNI (Indonesian National Standard) analysis and Regulation of the Minister of Public Works and Public Housing of the Republic of Indonesia Number 28/PRT/M/2016 concerning Guidelines for Unit Price Analysis of Public Works (Permen PUPR No. 28-2016). In this study, the analysis was carried out by comparing the labor coefficient of SNI 7394: 2008 and the Regulation of the Minister of Public Works and Housing No.20 of 2016 on column reinforcement work.